Developing genre-based Digital PowerPoint media for teaching job application letters: An ADDIE approach with ClassPoint integration - Mely Puspitasari; Ria Ariesta; Noermanzah Noermanzah (UIN Raden Mas Said Surakarta, 2026)
The integration of digital technology into language instruction remains a challenge for many teachers, particularly in designing interactive learning media that effectively support students’ language development. While PowerPoint is widely used in classrooms, its pedagogical potential is often underutilized due to limited interactivity and insufficient alignment with instructional approaches. This study aimed to develop and evaluate a genre-based digital PowerPoint learning medium integrated with the ClassPoint application for teaching job application letter texts to Grade XII senior high school students. The study employed a Research and Development (R&D) design using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation, student trials, and pretest–posttest assessments. The developed media was evaluated in terms of material quality, language appropriateness, instructional design, and learning effectiveness. The findings indicate that the developed media achieved a high level of feasibility based on expert evaluations and was effective in improving students’ language skills. Significant improvements were observed across listening, reading and viewing, speaking and presenting, and writing competencies, with N-gain scores ranging from 0.59 to 0.68, indicating moderate learning gains. The study demonstrates that ClassPoint-integrated genre-based digital PowerPoint media can enhance student engagement and learning outcomes while providing teachers with a practical and technology-enhanced instructional tool for language learning.